Ebola viral dynamics in nonhuman primates provides insights into virus immuno-pathogenesis and antiviral strategies - Vincent Madelain (Nature Portfolio, 2018)
Optimization of antiviral therapy can be crucial in the management of Ebola virus outbreaks. Here, Madelain et al. use an integrative mathematical model to correlate the dose and the time of treatment initiation with survival rate, enhanced immune response and viral clearance.